1990
DOI: 10.1159/000213172
|View full text |Cite
|
Sign up to set email alerts
|

Skin Thickness Changes in Normal Aging Skin

Abstract: The age-dependent decrease of skin thickness was studied with a morphometric procedure on upper inner arm skin biopsies. Epidermal thickness decreased somewhat faster in men (7.2 % of the original value/decade) than in women (5.7 %). The total dermal thickness decreased at about the same rate in men and women (6%/decade). The thickness of the superficial layer of the dermis exhibited a biphasic evolution with age and these variations were not significantly different between men and women because of the large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
3
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(152 citation statements)
references
References 12 publications
10
137
3
2
Order By: Relevance
“…As previously stated, however, all hormone-de®cient patients were receiving adequate substitution therapy. Epidermal thickness has been shown to decrease with age at a magnitude of approximately 6±7% per decade (17). The epidermal thickness found in the controls in the present study is comparable to that previously reported in healthy individuals of similar age (17).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As previously stated, however, all hormone-de®cient patients were receiving adequate substitution therapy. Epidermal thickness has been shown to decrease with age at a magnitude of approximately 6±7% per decade (17). The epidermal thickness found in the controls in the present study is comparable to that previously reported in healthy individuals of similar age (17).…”
Section: Discussionsupporting
confidence: 89%
“…Epidermal thickness has been shown to decrease with age at a magnitude of approximately 6±7% per decade (17). The epidermal thickness found in the controls in the present study is comparable to that previously reported in healthy individuals of similar age (17). In the present study, the GH-treated patients were comparable in age with the controls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In skin, for example, the outer epidermal layer is pigmented by melanin which absorbs strongly in the UV while the inner dermal layer is pigmented by blood which absorbs in the visible and near-infrared parts of the spectrum [26]. Furthermore, the thickness of the epidermal layer may vary with anatomical location, gender, and age [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…From a macroscopic point of view, aged skin differs from young skin with regard to wrinkles, elasticity, thickness (3,4), and surface pattern (5). Microscopic and biochemical analyses of aged skin indicate that the living epidermis comprises a smaller number of layers and that the dermal-epidermal junction is attened (5).…”
Section: Aging Of Human Skinmentioning
confidence: 99%